Long Acellular Nerve Allografts Cap Transected Nerve to Arrest Axon Regeneration and Alter Upstream Gene Expression in a Rat Neuroma Model. Issue 1 (July 2021) - Pan, Deng; Bichanich, Miles; Wood, Ian S.; Hunter, Daniel A.; Tintle, Scott M.; Davis, Thomas A.; Wood, Matthew D.; Moore, Amy M.
Abstract : Background: Treatments to manage painful neuroma are needed. An operative strategy that isolates and controls chaotic axonal growth could prevent neuroma. Using long acellular nerve allograft to "cap" damaged nerve could control axonal regeneration and, in turn, regulate upstream gene expression patterns. Methods: Rat sciatic nerve was transected, and the distal nerve end was reversed and ligated to generate a model end-neuroma. Three groups were used to assess their effects immediately following this nerve injury: no treatment (control), traction neurectomy, or 5-cm acellular nerve allograft cap attached to the proximal nerve. Regeneration of axons from the injured nerve was assessed over 5 months and paired with concurrent measurements of gene expression from upstream affected dorsal root ganglia. Results: Both control and traction neurectomy groups demonstrated uncontrolled axon regeneration revealed using Thy1-GFP rat axon imaging and histomorphometric measures of regenerated axons within the most terminal region of regenerated tissue. The acellular nerve allograft group arrested axons within the acellular nerve allograft, where no axons reached the most terminal region even after 5 months. At 5 months, gene expression associated with regeneration and pain sensitization, including Bdnf, cfos, and Gal, was decreased within dorsal root ganglia obtained from the acellular nerve allograft group compared to control or traction neurectomy group dorsal root ganglia. Conclusions: Long acellular nerve allografts to cap a severed nerve arrested axon regeneration within the acellular nerve allograft. This growth arrest corresponded with changes in regenerative and pain-related genes upstream. Acellular nerve allografts may be useful for surgical intervention of neuroma.